MERGERS, ACQUISITIONS AND DIVISIONS AND REFLECTION IN THE VALUE OF THE MARKET OF COMPANIES: A STUDY IN THE PERSPECTIVE OF CORE BUSINESS - Santana, Edílson Hélio (2016)
This article aims to evaluate the evolution of operating profit organizations before and after performing mergers, acquisitions or spin-offs, considering these activities as movements adjacent, or not, to its core business, based on Zook's theory (2003). For this, we used the exploratory research with a quantitative approach, through the selection of five emblematic cases. The results showed that organizations when presented expansion projects with adjacent movements close to the core business or when they realized divisions in order to better focus on their core business, appreciated by their actions in their respective stock exchanges.